IMPLEMENTASI SITUS WEBSITE DPRD DALAM MEMPUBLIKASIKAN AKTIVITAS ANGGOTA DPRD KOTA PEKANBARU - M. Eka Prasetya Hasibuan; Genny Gustina Sari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Websites are pages of information sites that can be accessed quickly. It is important for local governments to provide websites that can meet the needs of public services. The existence of Pekanbaru city DPRD website is a form of technological progress in supporting the process of delivering information to the public through their own media. The first Pekanbaru city DPRD website was inaugurated in 2013 with the domain name http://dprd-pekanbarukota.go.id. Many benefits from the use of the website, but the current phenomenon, where the Pekanbaru city DPRD website has not been updated since 2014-2016This type of research uses qualitative method. The determination of research subjects and informants using purposive techniques. In this study which became the researcher informant is Kabag. Public relations, Kasubag. Aspirations & information technology, public relations staff and representatives of legislators Pekanbaru city. While the object of this study is the implementation of the DPRD website in publicizing the activities of members of parliament pekanbaru city. Data collection techniques in this research is done through observation, interview, documentation and internet searching. The data analysis technique used in this research is using interactive model Miles and Huberman. Testing technique of data validity using triangulation tecgnique.The results of this study indicate that the city council website pekanbaru fakum because the government has decreased the budget so that it affects the operational budget, human resources are also less competent, facilities and infrastructure is absent so the 45 DPRD members and the completeness of the board can not be covered in news services. However, all efforts have been made to ensure that it is resolved, so the pekanbaru city DPRD website now runs smoothly and is always updated as a reliable informant in providing information to the public.Keyword : Implementation, Website, Publication, Public Relation, Government